(untitled) (Journal of Educational Management, 2016)
Effective use of instructional time has engaged the attention of many writers and researchers in recent times. This study investigated the effective use of instructional time in public senior high schools in the Northern Region of Ghana. 500 students were sampled from 7 public senior high schools to participate in the study. Three programmes of study, namely, general arts, general science, and home economics, were sampled for the study. The research design employed was a combination of a cross-sectional survey and the use of documentary evidence. The analysis was done using frequencies and a one-way ANNOVA. The analysis revealed that out of 364 days in a school year, only 177 days, representing 49% of the entire period, did public senior high schools engage in various school activities. The remaining 187 days, representing 51% of the period, were not used for any school learning activity. The findings further revealed that the three programmes of study were allocated equal amounts of time for classroom instruction. However, only 71% of this time is reflected in the school timetable as actual class engagement time. The majority of the students spent 58% of their entire school time actually engaged in classroom instruction. The study recommended that the Ghana Education Service should take steps to ensure improved efficiency with regard to the use of instructional time in public senior high schools. Efficiency in this regard can be improved by either reducing the number of school holidays in the year or reducing the hours spent on cocurricular activities to make room for more instructional hours.